Opportunities for harmonic cancellation with carrier-based PWM for a two-level and multilevel cascaded inverters - Holmes, D.G.; McGrath, B.P. (IEEE transactions on industry applications, 2001)
Pulsewidth modulation (PWM) strategies have been the subject of many years of research effort, and the merits of the various alternatives investigated have been argued extensively. In general, it is now accepted that natural or asymmetrical regular sampled PWM with a third harmonic injected or a space-vector centered reference waveform gives the best harmonic performance, with discontinuous modulation having some advantages for higher modulation ratios. This paper uses a general analytical solution for carrier-based PWM to mathematically identify the harmonic cancellation that occurs in various PWM implementations and converter topologies. This solution provides a formal justification for the superiority of natural and asymmetrical regular sampling techniques in eliminating half of their sideband harmonics simply by virtue of their phase leg switching. Then, the use of fundamental reference phase shifting between phase legs to create single- and three-phase 1-1 output voltages is reviewed, and the harmonic cancellation that occurs is identified. One significant result from this analysis is the realization that an odd/triplen carrier/fundamental ratio has no intrinsic harmonic benefit, contrary to the generally accepted wisdom. Finally, opportunities for harmonic elimination in multilevel cascaded inverter systems by carrier phase shifting are investigated, and the optimum phase shift is identified.